A nitrogenous pre-intercalation strategy for the synthesis of nitrogen-doped Ti3C2Tx MXene with enhanced electrochemical capacitance. Issue 10 (12th February 2021) - Yang, Fangli; Hegh, Dylan; Song, Dongxing; Zhang, Jizhen; Usman, Ken Aldren S.; Wang, Zhiyu; Zhang, Peng; Ma, Weigang; Yang, Wenrong; Qin, Si; Razal, Joselito M.
Abstract : A two-step pre-intercalation strategy is developed, using ammonium citrate as an all-in-one intercalant, antioxidant and nitrogen source, for producing nitrogen-doped Ti3 C2 T x MXene with improved electrochemical capacitance and high-rate performance. Abstract : Tremendous efforts have been dedicated towards high-performance energy storage devices though material innovation, nanoscale structural design and hybrid fabrication approaches. A crucial technique to tune the properties of nanomaterials, such as MXene, is through introducing defects or heteroatom dopants. To improve the level of nitrogen dopant, a two-step pre-intercalation–annealing strategy is developed herein, using ammonium citrate (AC) as an all-in-one intercalant, antioxidant and nitrogen source, followed by annealing in an ammonia atmosphere. It is shown that the doping efficiency of nitrogen-doped Ti3 C2 T x MXene (N-MXene) increased from 3.5% to 6.3%, compared with MXene annealed in ammonia without pre-intercalation. This high doping level induces significantly enhanced electrochemical capacitance (475 F g −1 at 5 mV s −1 ) compared with pristine MXene (321 F g −1 ), and greatly improved performance at high current density (248 F g −1 at 1 V s −1 ). Modelling was performed to elucidate the N-doping process of MXene and to understand the mechanism enhancing the electrochemical capacitance, which indicates that the pre-intercalation strategy promotes N-doping as surface functionalization, as well as in the MXene lattice. The pre-intercalation strategy demonstrates a new and facile pathway for functionalizing Ti3 C2 T x MXene which will facilitate use in applications such as in high performance supercapacitors.